Engineering Hierarchical CuO/WO3 Hollow Spheres with Flower-like Morphology for Ultra-Sensitive H2S Detection at ppb Level - Peishuo Wang; Xueli Yang (Chemosensors, 2025)
Highly sensitive real-time detection of hydrogen sulfide (H2S) is important for human health and environmental protection due to its highly toxic properties. The development of high-performance H2S sensors remains challenging for poor selectivity, high limit detection and slow recovery from irreversible sulfidation. To solve these problems, we strategically prepared a layered structure of CuO-sensitized WO3 flower-like hollow spheres with CuO as the sensitizing component. A 15 wt% CuO/WO3 exhibits an ultra-high response (Ra/Rg = 571) to 10 ppm H2S (131-times of pure WO3), excellent selectivity (97-times higher than 100 ppm interference gas), and a low detection limit (100 ppb). Notably, its fast response (4 s) is accompanied by full recovery within 236 s. After 30 days of continuous testing, the response of 15 wt% CuO/WO3 decreased slightly but maintained the initial response of 90.5%. The improved performance is attributed to (1) the p-n heterojunction formed between CuO and WO3 optimizes the energy band structure and enriches the chemisorption sites for H2S; (2) the reaction of H2S with CuO generates highly conductive CuS, which significantly reduces the interfacial resistance; and (3) the hierarchical flowery hollow microsphere structure, heterojunction, and oxygen vacancy synergistically promote the desorption. This work provides a high-performance H2S gas sensor that balances response, selectivity, and response/recovery kinetics.